The Interaction of Insulin with the Insulin Receptor in a Membrane Environment - Sabapathy, Thiruvarutchelvan (Curtin University, 2018)
The first event in insulin action is the binding of insulin to insulin-receptors embedded in the cell membrane. This study investigated how plasma membrane cholesterol influences this interaction, as examined in several experimental models including cultured cells, virus-like-particles and liver cell plasma membranes. The study is of relevance to a better understanding of diabetes at a molecular level. Novel results include the demonstration that alterations in membrane cholesterol content significantly reduce insulin binding and signalling.